2015
DOI: 10.1002/2014jd022732
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene emissions and impacts over an ecological transition region in the U.S. Upper Midwest inferred from tall tower measurements

Abstract: We present 1 year of in situ proton transfer reaction mass spectrometer (PTR-MS) measurements of isoprene and its oxidation products methyl vinyl ketone (MVK) and methacrolein (MACR) from a 244 m tall tower in the U.S. Upper Midwest, located at an ecological transition between isoprene-emitting deciduous forest and predominantly non-isoprene-emitting agricultural landscapes. We find that anthropogenic interferences (or anthropogenic isoprene) contribute on average 22% of the PTR-MS m/z 69 signal during summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 106 publications
(175 reference statements)
1
50
0
Order By: Relevance
“…The biomass burning emissions were from the Global Fire Emissions Database version 4 (Giglio et al, 2013). The biogenic VOC emissions were from the Model of Emissions of Gases and Aerosols from Nature version 2.1 inventory of Guenther et al (2012) as implemented in GEOS-Chem by Hu et al (2015). Emissions from other natural sources (e.g., lightning and volcanoes) were also included (Fisher et al, 2011;Murray et al, 2012).…”
Section: Geos-chem Aod Simulationmentioning
confidence: 99%
“…The biomass burning emissions were from the Global Fire Emissions Database version 4 (Giglio et al, 2013). The biogenic VOC emissions were from the Model of Emissions of Gases and Aerosols from Nature version 2.1 inventory of Guenther et al (2012) as implemented in GEOS-Chem by Hu et al (2015). Emissions from other natural sources (e.g., lightning and volcanoes) were also included (Fisher et al, 2011;Murray et al, 2012).…”
Section: Geos-chem Aod Simulationmentioning
confidence: 99%
“…As discussed in Jiang et al (2015) several previous studies have suggested that the MEGANv2.0 isoprene emissions are biased high over North America. Hu et al (2015) found that using the MEGANv2.1, together with an improved land cover distribution, in GEOS-Chem successfully reproduced isoprene observations in North America. However, the MEGANv2.1 inventory is not yet available in the GEOS-Chem adjoint model.…”
Section: Optimization On the Initial And Boundary Conditionsmentioning
confidence: 99%
“…Lightning NO x emissions are from Murray et al (2012), soil NO x emissions are from Hudman et al (2012), and biogenic VOC emissions are from the Model of Emissions of Gases and Aerosols from Nature (MEGAN) v2.1 from Guenther et al (2012) and implemented by Hu et al (2015b). To account for secondary organic aerosol (SOA), 10 % of monoterpene emissions by carbon are added to OC emissions as done by Park et al (2003).…”
Section: General Descriptionmentioning
confidence: 99%